Determinants of Consumer Preference for Local Brands: A Comprehensive Review of Recent Literature - Luong Dinh Thien Duc; Sitti Mujahida (Global Review of Tourism and Social Sciences, 2024)
This article presents a comprehensive review of recent literature on consumer preferences for local brands, focusing on 34 empirical studies published between 2018 and 2022. The study identifies key factors influencing consumers’ decisions to favor local brands over global alternatives by employing a systematic literature review method. These factors include cultural identity, emotional connection, and economic considerations, with a particular emphasis on the role of brand management, social identity theory, and consumer behavior in shaping preferences. The review highlights variations in consumer preferences across different geographic and economic contexts, especially in emerging markets, and explores the competition between local and global brands. The findings offer valuable insights for both researchers and practitioners, shedding light on the complex drivers behind local brand preferences and providing guidance for enhancing market competitiveness. This review also underscores the importance of ethnocentrism, nationalism, and strategic brand management in fostering local brand loyalty. Future research directions are suggested to further explore these determinants and their implications in diverse settings.